Association of Dental Fear with Caries Status and Self-Reported Dentition-Related Well-Being in Finnish Conscripts - Antti Kämppi; Tarja Tanner; Olavi Viitanen; Vesa Pohjola; Jari Päkkilä; Leo Tjäderhane; Vuokko Anttonen; Pertti Patinen (MDPI AG, 2022)
The main aim of this cross-sectional study was to examine the prevalence of dental fear among Finnish conscripts. Other aims were to study the association between dental fear and cariological status as well as their self-reported, dentition-related well-being. The study material consisted of 13,564 men and 255 women conscripts who underwent oral examinations. Of those, 8713 responded to a computer-based questionnaire. The mean number of decayed teeth (DT) was used in analyses for cariological status. Self-reported dental fear, dentition-related well-being and regular check-ups were analysed. Data were analysed with cross tables, Pearson Chi-Square tests, Fisher's exact test and binary logistic regressive analysis. High dental fear or finding dental visits very scary was associated with DT > 2 both among women (14.6%, when DT = 0; 33.3%, when DT > 2) and men conscripts (2.3% and 10.8%, respectively). In addition, those reporting that dental health had a negative impact on their well-being and had no regular check-ups were more likely to need cariological treatment than the rest. A high education level, both one's own and parental, was a protective factor for restorative treatment need in male conscripts. The findings of this study support the concept of a vicious cycle of dental fear and dental caries. A preventive, interactive way of work by dental teams would most likely be beneficial for dental health, avoiding the development of dental fear, and dentition-related well-being.